Importance of Gender on Long-Term Memory Ability (Eurasian Journal of Learning and Academic Teaching, 2023)
Maccoby and Jacklin's 1974 study on gender differences in human abilities and functions found that girls perform better in verbal ability, while boys excel in visuospatial and mathematical abilities. However, they rejected the hypothesis of gender differences in learning and memory. Recent research has shown that females tend to outperform males in memory, with 17 out of 64 reviewed experiments showing significant differences favoring females. This pattern has been observed in various studies, including those conducted in Europe or America. The study conducted in Tashkent, Uzbekistan, aims to challenge the long-standing notion of male superiority over females in memory and examines both implicit and explicit memories, two types of long-term memory, to determine if females can outperform males in long-term memory itself. The study involved a cohort of 40 volunteers from the same geographic locale and shared educational backgrounds. The study investigated semantic memory, episodic memory, and implicit memory in high school students. Participants were asked to memorize ten Chinese words and recite them to the best of their recollection. The results showed slight differences between genders in memory abilities. Females had a higher facility for acquiring new information and superior performance in semantic memory. In episodic memory, females showed a superior aptitude compared to males. Only nine out of twenty males were able to recall their first meeting with a close friend, while nearly fourteen out of twenty females provided intricate narratives. The study also found that females attained an average accuracy rate of 97 out of 100 percent in implicit memory tests, while males achieved an average accuracy rate of 95.8 out of 100 percent. These findings suggest that females have superior long-term memory abilities compared to males within the age range of 15-18 in Uzbekistan. However, it is essential to note that gender differences in memory abilities may vary across different age groups.